METODE PEMBAGIAN WARIS TERHADAP ISTRI KEDUA PERSPEKTIF KOMPILASI HUKUM ISLAM DAN HUKUM PERDATA : (STUDI KOMPARATIF) - Hafidz Miftahuddin, Abdul (USRATUNA: Jurnal Hukum Keluarga Islam, 2019)
Inheritance is a collection of regulations governing the law regarding wealth because of one's death, which is the transfer of wealth left by the dead and the consequences of this transfer for those who obtain it both in their relationship with them, as well as their relationship with third parties. The main purpose of inheritance is either in the Compilation of Islamic Law or civil law is to provide welfare and justice for heirs based on the principles and legal basis of each. The distribution of inheritance to the second wife according to the Compilation of Islamic Law and Civil Law has similarities and differences. The elements in inheritance according to the Compilation of Islamic Law and civil law are the same or hand in hand and complement each other, nothing contradicts. However, in some cases there are differences, one of which is in the division and number of parts for heirs. Also for the second wife, the two laws differ in looking at her. Islam views the second wife as being the same as the other wives as long as there are no children, but civil law views that the part for the second wife must not be more than the child of the first wife.